The ongoing violence against women: Female Genital Mutilation/Cutting - Muteshi, Jacinta K. (2016)
Female Genital Mutilation/Cutting (FGM/C) comprises different practices involving cutting, pricking, removing and sometimes sewing up external female genitalia for non-medical reasons. The practice of FGM/C is highly concentrated in a band of African countries from the Atlantic coast to the Horn of Africa, in areas of the Middle East such as Iraq and Yemen, and in some countries in Asia like Indonesia. Girls exposed to FGM/C are at risk of immediate physical consequences such as severe pain, bleeding, and shock, difficulty in passing urine and faeces, and sepsis. Long-term consequences can include chronic pain and infections. FGM/C is a deeply entrenched social norm, perpetrated by families for a variety of reasons, but the results are harmful. FGM/C is a human rights issue that affects girls and women worldwide. The practice is decreasing, due to intensive advocacy activities of international, national, and grassroots agencies. An adolescent girl today is about a third less likely to be cut than 30 years ago. However, the rates of abandonment are not high enough, and change is not happening as rapidly as necessary. Multiple interventions have been implemented, but the evidence base on what works is lacking. We in reproductive health must work harder to find strategies to help communities and families abandon these harmful practices.